Ikoon en Medium: die toneelpop, masker en akteurmanipuleerder in Afrika-performances - Du Preez, Petrus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DPhil (Drama)--University of Stellenbosch, 2007.